Llama Llama : Llama family vacation [videorecording (DVD)] - Dewdney, Anna; Duncan, Reed; Startz, Jane (Llama Llama., 2021)
Join Llama Llama, Nelly Gnu, Luna Giraffe, Euclid the Sheep, and Gilroy Goat as they explore their friendly hometown and make childhood memories. On this DVD Llama Llama is preparing to go on his first vacation and plane ride with Mama Llama and Gram to visit Cousin Llama and his daughter, Libby Llama, where they live, on Sandy Island. It's a vacation of many "firsts" for Llama Llama.